The US Decision to Withdraw Its Forces from Afghanistan: Analyzing the Pakistani Media Approach in the Context of Policy Debate Jamaluddin1 and Painda (Journal of Asian Development Studies, 2023)
To investigate the connections between the government and media, this study examines how the Pakistani media has covered the policy issue of the U.S. forces' withdrawal from Afghanistan. The primary conclusions of the research validate the central tenets of the mediapolicy interaction model (Robinson, 2000, 2017). The Pakistani media primarily promoted "peace journalism," calling on the international community to devise plans for turning wartorn Afghanistan into a peaceful nation while also conveying the concerns of policymakers [the elite consensus, which is the premise of Bennett's indexing theory] regarding the policy issue of Afghanistan. The way Pakistan views Afghanistan in terms of its top policy priorities is reflected in the way that the Pakistani media framed the withdrawal of U.S. forces from a peace journalism perspective.